2015
DOI: 10.3168/jds.2015-10104
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and partial characterization of bacteriocin-like inhibitory substances produced by Lactobacillus spp. isolated from artisanal Mexican cheese

Abstract: Lactobacillus spp. from Mexican Cocido cheese were shown to produce bacteriocin-like substances (BLS) active against Staphylococcus aureus,Listeria innocua,Escherichia coli, andSalmonella typhimurium by using the disk diffusion method. Crude extracts of Lactobacillus fermentum showed strong inhibitory activity against Staph. aureus, L. innocua, E. coli, and Salmonella cholerae. Complete inactivation of antimicrobial activity was observed after treatment of crude extracts with proteinase K, pronase, papain, try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 30 publications
5
47
0
3
Order By: Relevance
“…The inactivation of inhibitory activity of antibacterial compound after treatment with proteolytic enzyme is indicative of presence of BLIS. This is in agreement with several reports, which used similar term for antimicrobial compounds produced by LAB, which were susceptible to proteolytic enzymes (Corsetti, Settanni, & Van Sinderen, ; Ghanbari, Jami, Kneifel, & Domig, ; Heredia‐Castro et al, ).…”
Section: Resultssupporting
confidence: 93%
“…The inactivation of inhibitory activity of antibacterial compound after treatment with proteolytic enzyme is indicative of presence of BLIS. This is in agreement with several reports, which used similar term for antimicrobial compounds produced by LAB, which were susceptible to proteolytic enzymes (Corsetti, Settanni, & Van Sinderen, ; Ghanbari, Jami, Kneifel, & Domig, ; Heredia‐Castro et al, ).…”
Section: Resultssupporting
confidence: 93%
“…In Southeastern region of Serbia, inhabitants produce one type of autochthonous cheese, called Sokobanja cheese using raw, unpasteurized cow's milk without adding the bacterial starter culture. Therefore, lactic acid bacteria (LAB) from this cheese (native microflora) mediate fermentation processes and could be used to inhibit pathogenic or spoilage microorganisms (Heredia‐Castro et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that antagonistic action of lactobacilli against selected undesirable or pathogenic microorganisms, which are hazardous as contaminant, was significant. Using the disk diffusion method, Heredia‐Castro et al () showed that crude extracts of Lb. fermentum showed strong inhibitory activity against S. aureus , L. innocua , E. coli , and Salmonella cholerae .…”
Section: Discussionmentioning
confidence: 99%